Wellness : concepts and applications - Anspaugh, David J.; Hamrick, Michael H.; Rosato, Frank D. (New York : McGraw-Hill Higher Education, 2011)
'Wellness: Concepts and Applications uses the basic precepts of the wellness movement-- personal responsibility, behavior change and risk reduction, and health-care consumer awareness--to introduce students to the health- and wellness-related information they need to thrive in today's world. The authors provide accurate, scientifically based information on wellness topics as well as assessment activities and other tools for behavior change. The authors also provide a balance among the seven dimensions of wellness while at the same time emphasizing the central roles of physical fitness, nutrition, avoidance of tobacco, and stress management as keys to a healthy life. Other fitness and wellness topics include body composition, flexibility, safety, drugs, STDs, chronic diseases, and more. Accompanying the text are instructor and student resources on the Online Learning Center'--
Machine generated contents note: 1 Wellness and Fitness for Life 2 Preventing Cardiovascular Disease 3 Increasing Cardiorespiratory Endurance 4 Building Muscular Strength and Endurance 5 Improving Flexibility 6 Forming a Plan for Good Nutrition 7 Understanding Body Composition 8 Achieving a Healthy Weight 9 Coping with and Managing Stress 10 Taking Charge of Your Personal Safety 11 Taking Responsibility for Drug Use 12 Preventing Sexually Transmitted Diseases 13 Understanding Cancer and Diabetes 14 Becoming a Responsible Health Care Consumer
Includes bibliographical references and index.
Keywords: Health; Self-care, Health; Medicine, Preventive